Evaluate the predictive accuracy of cvp/lap ratio for weaning from cpb in cabg surgery - Fareed, Dr Zainab; Muhammad Azeem Mir; Kaneez ume Farwa; Muhammad Hamid Chaudhary (Medical Journal of South Punjab, 2025)
Objective: This study aimed to evaluate the predictive accuracy of the CVP/LAP ratio for successful weaning from CPB in patients undergoing CABG surgery.Methods: A prospective observational study was conducted involving 40 patients undergoing elective CABG surgery at the Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC) in Multan, Pakistan. Pre-pump and post-weaning CVP and LAP were measured, and the CVP/LAP ratio was calculated. Logistic regression analysis was used to assess the predictive value of the CVP/LAP ratio, and a receiver operating characteristic (ROC) curve was generated to evaluate its discriminative ability.Results: The mean pre-pump CVP/LAP ratio was 0.83 (SD = 0.28). Logistic regression analysis showed that the CVP/LAP ratio had an overall predictive accuracy of 80% for successful weaning. However, the area under the ROC curve (AUC) was 0.68, indicating moderate discriminative power. The model failed to correctly classify unsuccessful weaning cases, highlighting limitations in using the CVP/LAP ratio as a standalone predictor.Conclusions: The CVP/LAP ratio demonstrates moderate predictive accuracy for successful weaning from CPB in CABG surgery. However, its limitations suggest that it should be integrated into a broader clinical assessment rather than used in isolation. Further research is needed to develop more comprehensive predictive models.